2014
DOI: 10.1007/s00464-014-3556-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring c-reactive protein after laparoscopic colorectal surgery excludes infectious complications and allows for safe and early discharge

Abstract: Monitoring CRP level in laparoscopic colorectal surgery demonstrated a high diagnostic accuracy for infectious complications, thus allowing for safe and early discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…Although no single inflammatory marker can definitively exclude an anastomotic leak, routine measurement of CRP concentration with use of the suggested cut‐off levels may allow safe discharge. As shown recently in a large series of laparoscopic colonic resections, clinical signs of postoperative infectious complications are rarely apparent before POD 6.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although no single inflammatory marker can definitively exclude an anastomotic leak, routine measurement of CRP concentration with use of the suggested cut‐off levels may allow safe discharge. As shown recently in a large series of laparoscopic colonic resections, clinical signs of postoperative infectious complications are rarely apparent before POD 6.…”
Section: Discussionmentioning
confidence: 83%
“…Measurement of CRP levels is widely available and well established in routine clinical practice, unlike procalcitonin or IL‐6, other recently described markers of systemic inflammation. The predictive value of postoperative CRP levels to rule out infectious complications after colorectal, bariatric, gastro‐oesophageal and pancreatic surgery has been assessed previously.…”
Section: Introductionmentioning
confidence: 99%
“…However, one paper reported no differences in CRP levels between the AL and non-AL groups after total colectomy for familial adenomatous polyposis [16] . Serum CRP levels are influenced by infectious complications such as pneumonia, urinary tract infections, and wound infections [17] . Moreover, a 398 systematic review and meta-analysis reported that the positive/negative predictive values of CRP for AL were 21-23 and 97%, respectively, and concluded that CRP is a useful negative predictor of AL [18] .…”
Section: Discussionmentioning
confidence: 99%
“…This fact enhances the interest of absolute values over tendencies, as it has already been stated in previous works having explored the interest of thresholds and that of decrements. 25,26 It is well established that most postoperative infections become clinically evident beyond POD 5, with advanced IAI. CRP was more accurate than PCT, as it was the case in several previous smaller series.…”
Section: Table 2 Daily Levels (Medians and Interquartilic Ranges) Ofmentioning
confidence: 99%